Pengaruh Etos Kerja, Iklim Kerja dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan Warung Padang Upik Yogyakarta - Ocsalino Damare; Prayekti Prayekti; Epsilandri Septyarini (Universitas Batanghari Jambi, 2023)
The research aims to analyze employee performance as influenced by work motivation, climate, and work ethic. Then the technique implemented in sampling is a saturated sample and research data is collected through questionnaires. Furthermore, the researcher applied multiple linear regression testing methods to analyze the data. Based on the test results, the dependent variable, namely work performance is significantly positively influenced by the independent variable, namely, work motivation, work climate, and work ethic.